Does Bank Size Matter? A Comparative Study of Risk, Return and Efficiency in Islamic Banking - Fira Nurafini; Arfiana Meilani Andrayuni (Indonesian Journal of Islamic Economics and Finance, 2025)
This study examines whether bank size influences differences in risk, return, and operational efficiency in Islamic commercial banks in Indonesia. Despite the rapid growth of the Islamic banking sector, performance disparities among banks remain evident, raising questions about the role of bank size in shaping financial outcomes. The aims of this study is to analyze the performance of Islamic banks based on their size classifications. This research employs a quantitative comparative approach using panel data from 12 Islamic commercial banks over the period of 2021–2025. Bank size is categorized into four groups based on core capital, while risk, return, and efficiency are measured using Non-Performing Financing (NPF), Return on Assets (ROA), and Cost to Income Ratio (CIR), respectively. The analysis utilizes non-parametric statistical methods, particularly the Kruskal–Wallis test, due to non-normal data distribution. The findings reveal significant differences in risk, return, and operational efficiency across bank size groups. Smaller banks tend to exhibit higher risk, lower profitability, and lower efficiency, while medium-sized banks demonstrate the highest profitability and better efficiency. However, larger bank size does not always guarantee superior performance, indicating the presence of other influencing factors. In conclusion, bank size plays an important but not exclusive role in determining Islamic bank performance, highlighting the need for effective risk management and operational strategies.